2020
DOI: 10.1002/joc.6772
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐latitude leading double‐dip La Niña

Abstract: Understanding the evolution asymmetry between El Niño and La Niña events is challenging. Unlike El Niño, most La Niña events are characterised by a double-dip cooling (a.k.a. multi-year La Niña). Herein, we examined how single-and multi-year La Niña events differ by analysing observational and climate-model data sets. Single-year La Niña events tend to develop narrowly within the tropics from a central Pacific-type El Niño (Niño-4 > Niño-3), whereas multi-year La Niña events tend to originate from an eastern P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
(91 reference statements)
4
29
0
Order By: Relevance
“…We confirmed that the identical sets of events were obtained using the Ocean Niño Index provided by NOAA ( https://origin.cpc.ncep.noaa.gov/products/analysis_monitoring/ensostuff/ONI_v5.php ), and also that all La Niña events occurred after El Niño in the previous year. Despite a difference in the SST data, extracted events are consistent with past multi-year La Niña studies 27 , 50 . When multi-year La Niña lasted for three years, we analyzed the first two years.…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…We confirmed that the identical sets of events were obtained using the Ocean Niño Index provided by NOAA ( https://origin.cpc.ncep.noaa.gov/products/analysis_monitoring/ensostuff/ONI_v5.php ), and also that all La Niña events occurred after El Niño in the previous year. Despite a difference in the SST data, extracted events are consistent with past multi-year La Niña studies 27 , 50 . When multi-year La Niña lasted for three years, we analyzed the first two years.…”
Section: Methodssupporting
confidence: 79%
“…However, our results clearly show that multi-year La Niña is not a statistical artefact but a part of the intrinsic complex nature of ENSO. Previous studies have shown the contribution of anomalous wind stress curl causing GHT in the ENSO transition 12 , 24 , 35 37 , an active role of inter-basin interaction for the transition asymmetry 38 , and a meridional shift of westerly surface wind anomalies for the transition from strong El Niño to La Niña 16 18 , 39 . Although we do not exclude these processes during ENSO phase transition, we demonstrate that the anomalous Ekman heat transport is crucial to transition from strong El Niño to multi-year La Niña.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The double peak feature is a result of the seasonal modulation of the growth rate. The double peak of ENSO can be found in observation as well (Cole et al 2002;Okumura and Deser 2010;Park et al 2021). We classify these two peaks based on their intensities; primary and secondary peak.…”
Section: Modulation Of the Enso Peak Calendar Monthmentioning
confidence: 89%
“…For example, Okumura and and Deser (2010) argued that Indian Ocean capacitor effect (Xie et al 2009) weakens ENSOinduced western-Pacific winds during the mature phase of ENSO through atmospheric teleconnection, and this remote impact is more effective during La Nina, because La Ninainduced easterly winds are located in the western Pacific, while El Nino-induced westerly winds are located in the central Pacific. Park et al (2021) suggested that the multi-year La Niña is related to a strong connection between the tropical Pacific and mid-latitude Pacific through Pacific Meridional Mode, which weakens the off-equatorial wind stress curl over western Pacific as well as consequent oceanic heat recharge leading a weaker termination of the first peak event. Such complex physical processes can be incorporated to single SEI framework, indicating anomalously high SEI due to weaken SST damping process after first peak (Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%